Protective Effect of Saccharides on Freeze-Dried Liposomes Encapsulating Drugs - Guimarães, Diana; Noro, Jennifer; Silva, Carla; Cavaco-Paulo, Artur; Nogueira, Eugénia (Frontiers in Bioengineering and Biotechnology, 2019)
The production of freeze-dried liposomes encapsulating drugs is considered a key challenge since the drugs are prone to leakage. The aim of this work was to study the effect of different saccharides on preserving the stability and drug retention capacity of a previously developed liposomal formulation, when subjected to a freeze-drying process. The protective role of trehalose, lactose, glucose, mannitol and sucrose, known for their cryo/lyoprotective effect, was tested by addition of different concentrations to liposomes. Sucrose, in a concentration dependent manner (8:1 sugar:lipids mass ratio) proved to be a suitable cryo/lyoprotectant of these liposomes. Effectively, this saccharide prevents the fusion or/and aggregation of the liposomal formulation, protecting the integrity of the freeze-dried empty liposomes. The liposomal formulation containing sucrose was studied in terms of morphology, concentration and anticancer drugs retention ability. The study involved two drugs encapsulated in the aqueous core, methotrexate (MTX) and doxorubicin (DOX), and one drug located in the lipid bilayer, tamoxifen (TAM). After the freeze-drying process, liposomes with sucrose encapsulating drugs revealed high physical stability, maintaining their narrow and monodisperse character, however high leakage of the drugs encapsulated in the aqueous core was observed. Otherwise, no significant drug leakage was detected on liposomes containing the TAM, which maintained its biological activity after the freeze-drying process. These findings reveal that sucrose is a good candidate for the cryo/lyoprotection of liposomes with drugs located in the lipid bilayer.